Pengaruh Budaya Organisasi, Kompetensi dan Beban Kerja Terhadap Kinerja Karyawan Konsultan Supervisi PT Catur Bina Guna Persada KSO pada Proyek Bendungan Leuwikeris Kabupaten Ciamis dan Kabupaten Tasikmalaya - Ading Rahman Sukmara; Seger Swarsono; Irma Bastaman (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
PT Catur Bina Guna Persada continues to improve its performance in accordance with its vision, namely building a healthy business climate with integrity, creativity and innovation. However, the reality is still not in accordance with what the company expects, there are various obstacles that occur such as organizational culture, low competence and high workloads are suspected to be factors that cause employee performance to be less than optimal. This study aims to determine and analyze the extent of the influence of organizational culture, competence and workload on the performance of employees of the PT Catur Guna Bina Persada KSO Supervision Consultant on the Leuwikeris Dam project in Ciamis Regency and Tasikmalaya Regency. Therefore, this study uses a quantitative approach with an explanatory method. This study uses primary data obtained directly through questionnaires distributed to employees of the PT Catur Guna Bina Persada KSO Supervision Consultant on the Leuwikeris Dam project in Ciamis Regency and Tasikmalaya Regency. The statistical method used is path analysis assisted by SPSS (Statistical Product and Service Solutions) Version 16.0 for Windows. Based on the calculation results obtained the R2 (R Square) figure, the influence of organizational culture, competence and workload on the performance of employees of the Supervision Consultant PT Catur Guna Bina Persada KSO on the Leuwikeris Dam project in Ciamis Regency and Tasikmalaya Regency is 49.6%, the influence of organizational culture on employee performance is 0.067%, the influence of competence on employee performance is 20.34%, the influence of workload on employee performance is 18.23%. Based on the hypothesis test, the results are that there is an influence of organizational culture, competence and workload on the performance of Supervision Consultant Employees of PT Catur Guna Bina Persada KSO on the Leuwikeris Dam project in Ciamis Regency and Tasikmalaya Regency, both partially and simultaneously. ational economy. This study aims to determine and describe the role of BUMDes in increasing village original income and utilizing village potential in Ciamis District. With the formulation of the problem how is the role of BUMDes in increasing village original income and utilizing village potential in Ciamis District. This study uses a qualitative descriptive research method. While data collection techniques through observation, interviews, documentation, and triangulation. Based on the results of the study and discussion, the following are concluded. The role of BUMDes in increasing Village Original Income in Ciamis District seen from three indicators, namely increasing village cash, emerging SMEs and increasing investment, has been in accordance with the provisions, although there are still many shortcomings. The role of BUMDes in Utilizing Village Potential in Ciamis District is seen from the aspect of being carried out through data collection and initial studies of available potential data to determine objects that can be utilized. Conducting field surveys to collect data that will be used as material in mapping potential and problems as well as facilities that will be implemented. Conducting studies through tabulation and analysis of collected data using established analysis methods. Determining the priority scale of potential to be developed based on needs, costs and benefits from the development results.